1996
DOI: 10.1046/j.1365-2249.1996.d01-721.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced binding of lymphocytes from patients with multiple sclerosis to tumour necrosis factor-alpha (TNF-α)-treated endothelial monolayers: associations with clinical relapse and adhesion molecule expression

Abstract: SUMMARYThis study investigated the adherent properties and adhesion molecule expression of blood mononuclear cells (MNC) from a total of 84 patients with multiple sclerosis (MS). The MNC from MS patients were significantly more adherent than cells from normal healthy subjects to endothelial monolayers pretreated with 0 . 01 U/ml TNF-® (103% increase; P 0 . 002), 0 . 1 U/ml TNF-® (80% increase; P < 0 . 01) and 1 . 0 U/ml TNF-® (41% increase; P < 0 . 02), and to endothelium pretreated with 10 U/ml IL-1¯(44% incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…These data are in agreement with those reported by Tsukada et al [22] and Vora et al [23], who found enhanced adhesion to cerebral endothelium only in patients in relapse and in chronic-progressive MS patients. The long-lasting reduction in adhesion phenomena between PBMNCs from IFN-β 1b -treated MS patients and endothelium, however, speaks in favor of a possible inhibiting effect of in vivo IFN-β 1b on the formation of perivascular infiltrates, at least partly mediated by modulation of adhesion molecules.…”
Section: Discussionsupporting
confidence: 94%
“…These data are in agreement with those reported by Tsukada et al [22] and Vora et al [23], who found enhanced adhesion to cerebral endothelium only in patients in relapse and in chronic-progressive MS patients. The long-lasting reduction in adhesion phenomena between PBMNCs from IFN-β 1b -treated MS patients and endothelium, however, speaks in favor of a possible inhibiting effect of in vivo IFN-β 1b on the formation of perivascular infiltrates, at least partly mediated by modulation of adhesion molecules.…”
Section: Discussionsupporting
confidence: 94%
“…Following cell activation CD62L is cleaved from the surface [21,22] and this effect may have contributed to its decreased distribution and low level of expression on CD4 + and CD8 + T lymphocytes during the thawing of cryopreserved cells. Additional studies by our group show that cryopreservation does not alter the adhesive properties of T lymphocytes for cultured endothelium in a static adherence assay [23] and for blood vessel walls exposed in tissue sections of normal brain. However, the same caveat is unlikely to apply to the ‘tethering’ of T lymphocytes to endothelial cells and to recognition of addressins on high endothelial venules, since each of these events is dependent upon CD62L expression.…”
Section: Discussionmentioning
confidence: 99%